2021
DOI: 10.1177/03000605211032807
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm-associated antigen 4 as a potential prognostic biomarker of lung squamous cell carcinoma

Abstract: Objective Lung cancer (LC) is one of the most prevalent malignant tumors worldwide. As a subtype of LC, lung squamous cell carcinoma (LUSC) has a 5-year survival rate of less than 15%. In this study, we aimed to evaluate the prognostic value of a glycolysis-related gene signature in LUSC patients. Methods We obtained RNA-Seq data from The Cancer Genome Atlas (TCGA) database. Prognosis-related genes were screened out by Gene Set Enrichment Analysis (GSEA) and Cox proportional regression models. Quantitative rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In view of the poor prognosis of patients with LUSC and the high tumor recurrence rate after resection, investigations on risk factors for tumor prognosis and recurrence are warranted, so as to support early intervention, improve monitoring, reduce tumor recurrence rate, and prolong patient survival time 15 , 16 . On account of the close relationship between blood lipids and tumorigenesis or tumor recurrence, we were interested to see if a relationship existed between lipid profile and the prognosis of Chinese patients with LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the poor prognosis of patients with LUSC and the high tumor recurrence rate after resection, investigations on risk factors for tumor prognosis and recurrence are warranted, so as to support early intervention, improve monitoring, reduce tumor recurrence rate, and prolong patient survival time 15 , 16 . On account of the close relationship between blood lipids and tumorigenesis or tumor recurrence, we were interested to see if a relationship existed between lipid profile and the prognosis of Chinese patients with LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the functional enrichment analysis revealed that immune-activating pathways were significantly enriched in low-risk NSCLC patients, whereas high-risk NSCLC patients were closely implicated in cell proliferation related functions. Indeed, several important BRGs found in BRGPs signature, such as BIRC3, IFT57, GADD45B and SPAG4, have been associated with the proliferation or migration of NSCLC cells (41,42,(58)(59)(60)(61). Therefore, high-risk NSCLC patients are more likely to harbor genome instability status and associated with high TMB, tumor progression, and relative advanced tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with lung adenocarcinoma, LUSC usually metastasizes later and are diagnosed at an advanced stage (Chen and Dhahbi 2021, Li, Kuang et al 2022). Moreover, patients with LUSC suffer from an adverse prognosis, with a 5-year survival rate of less than 15% (Wang, Tang et al 2021). Despite efforts to study the molecular basis of LUSC, the treatment landscape has barely changed in decades, and effective targeted therapies are still lacking.…”
Section: Introductionmentioning
confidence: 99%